Leukemia inhibitory factor (LIF) regulates JAK/STAT and canonical Wnt/β-catenin signaling pathways during murine embryo implantation. - Yee, Li Xuan. (2013)
Embryo implantation is the most critical stage in mammalian pregnancy. A key factor governing this process is the cytokine, Leukemia Inhibitory Factor (LIF). In mice, LIF acts on the uterine luminal epithelium (LE) converting it from a non-responsive epithelium to an embryo-responsive one. The LE expresses the LIF receptor (LIFR) complex and upon stimulation by LIF, it predominantly activates the JAK/STAT pathway. However the precise sequence of events involved in such activation is unknown. We therefore employed immunofluorescence and Western blot analysis to study the sequential events involved in the activation of this pathway. Our results indicate that LIF binds to the LIFR-gp130 receptor complex, thereby phosphorylating the STAT3 transcription factor and inducing its nuclear translocation within an hour in the LE.